On the Frontiers of Climate and Environmental Change Vulnerabilities and Adaptations in Central Vietnam - Bruun, Ole.; Casse, Thorkil; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book is intended to fill a gap in climate-change literature by providing a comprehensive regional study and identifying the overall adaptation challenges in a real-life context. The way in which possible climate impacts interact with a range of other challenges in agriculture, forestry, disaster planning, health care, general economic development, and common livelihoods are presented, and it is argued that greater realism and broader vision are needed in order to address the climate challenge. For instance, unsuitable land- use changes in both coastal and highland regions may increase the vulnerability of rural people, many of whom are already living on the fringes. The author(s) also state(s) that, depending on context, it may be pertinent to address short-term and unsustainable resource use, irregularities in local land management, ineffective governance and social inequality, which are all likely to aggravate the impact of external climate and weather. Not least, it is imperative to integrate general environmental management with any climate-change adaptation effort.
From the Contents: Introduction: Adaptation to climate and environmental change in Central Vietnam -- Paradoxes in adaptation: Economic growth and socio-economic differentiation -- Is climate change a reality for agriculture in Quang Nam province? -- The Push for plantations: Drivers, rationales and social vulnerabilities in Quang Nam province -- Climate change impacts on natural hazards in mid-central Vietnam: Flood, drought and landslide -- Impediments to climate-induced disaster management: Evidence from Quang Nam, Central Vietnam.
Keywords: Geography; Earth Sciences; Environmental Science and Engineering; Climate Change Impacts; Cultural Studies